THE CHRONICLE OF TERRORISM AND ISLAMIC MILITANCY IN INDONESIA - Zakiyah Zakiyah (Analisa: Journal of Social Science and Religion, 2016)
This paper examines the chronicle of terrorism in Indonesia and the relationshipbetween terrorism and Islamic militancy in this nation. This research focusedon bombing cases from 2001 to 2012 Data was gathered through documentaryresearch including primary and secondary resources. This research shows thatafter the fall of the Suharto regime in 1998, there were bomb attacks on varioustargets and militant extremists were able to return to Indonesia after long periodof exile abroad. They started again their activities including disseminating theirradical ideology, building networks and recruiting new members in Indonesia, aswell as preparing for militant actions. The perpetrators of these terror attacks weremostly associated with the Islamic radical groups like Jemaah Islamiah and MajlisMujahidin Indonesia. These two militant groups had a close relationship with DarulIslam, an organization founded during the colonial era that aimed to establish anIslamic state and to apply Syariah as a state law. In addition, both groups became apolitical window for al-Qaeda in Indonesia.